Pengaruh Metode Mind Mapping Terhadap Hasil Belajar IPA - Hasmawati, Hasmawati; Junaidi, Ilham Arvan; Ayu, Imelda Ratih (Social Science Academic, 2024)
This study aims to determine whether there is a significant difference in student learning outcomes in science lessons students who take lessons using the Mind Mapping method with students who take conventional learning in class V SD Negeri 17 Kayuagung. This type of research is an experiment. The research sample used total sampling, where the number of students in class VA was 25 and class VB was 26 students. With a total of 51 students. The data analysis used to analyze the research results is the t-test. based on the results of research data analysis it can be concluded that there is a significant difference in the science learning outcomes of students who take lessons using the Mind Mapping method with students who take conventional learning for fifth grade students at SD Negeri 17 Kayuagung. This is proven by the results of tcount more than ttable, namely 6.189> 1.666 with the acquisition of the average value of science learning outcomes in the experimental class higher than the control class. Thus the Mind Mapping method has a significant influence on the science learning outcomes of fifth grade students at SD Negeri 17 Kayuagung for the 2022/2023 academic year.